China's data protection legislation and its impact on multinational corporations - Korpineva, Sara (My University, 2025)
The collection and utilization of data has significantly increased, creating risks to the security of countries and individuals. Due to these new threats, many countries, including China, have implemented data protection laws to safeguard national security. China's data protection legislation poses challenges for multinational corporations operating in the Chinese market. This bachelor’s thesis focuses on the impact of China’s data protection legislation on multinational corporations and provides an analysis of existing academic literature on China’s data protection legislation and its impacts. The aim of this literature review is to understand the impacts that China’s data protection legislation has on multinational corporations’ business operations, focusing on the regulatory challenges posed by the Cyber Security Law (CSL), the Data Security Law (DSL), and the Personal Information Protection Law (PIPL). The research findings indicate that multinational corporations encounter significant challenges to comply with China’s three key data protection laws. These challenges primarily arise from the complexities of cross-border data transfer and data localization requirements. These requirements restrict market access and diminish the competitiveness of multinational corporations, leading to higher operational costs and increased legal risks.

Datan kerääminen ja hyödyntäminen on kasvanut merkittävästi, luoden riskejä maiden ja yksilöiden turvallisuudelle. Näiden uusien uhkien vuoksi monet maat, kuten Kiina, ovat kehittäneet tietosuojalakeja turvaamaan maata ja sen kansalaisia. Kiinan tietosuojalainsäädäntö luo suuria haasteista monikansallisille yrityksille, jotka toimivat Kiinan markkinoilla. Tämä kandidaatintutkielma keskittyy Kiinan tietosuojalainsäädännön vaikutuksiin monikansallisille yrityksille ja tarjoaa analyysin olemassa olevasta akateemisesta kirjallisuudesta, joka käsittelee Kiinan tietosuojalainsäädäntöä ja sen vaikutuksia. Tämän kirjallisuuskatsauksen tavoitteena on ymmärtää, millaisia vaikutuksia Kiinan tietosuojalainsäädännöllä on monikansallisten yritysten liiketoiminnoille, keskittyen erityisesti kyberturvallisuuslain (CSL), tietoturvalain (DSL) ja henkilötietojen suojauslain (PIPL) asettamiin sääntelyhaasteisiin. Tutkimustulokset osoittavat, että monikansalliset yritykset kohtaavat merkittäviä haasteita Kiinan kolmen keskeisimmän tietosuojalain noudattamisessa. Nämä haasteet johtuvat pääasiassa rajat ylittävän tiedonsiirron ja datan paikallistamisvaatimusten monimutkaisuudesta. Vaatimukset rajoittavat markkinoille pääsyä ja heikentävät monikansallisten yritysten kilpailukykyä, joka johtaa korkeampiin toiminnan kustannuksiin ja lisääntyneisiin oikeudellisiin riskeihin.
Keywords: China, data protection legislation, multinational corporation, Kiina, tietosuojalainsäädäntö, monikansallinen yritys